2020
DOI: 10.3389/fphy.2020.00365
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Secondary Neutron Field Produced in a Thick Aluminum Shield by 1 GeV/u 56Fe Ions Using TLD-Based Ambient Dosimeters

Abstract: The neutron ambient dose equivalent induced by galactic cosmic-ray-like (1 GeV/u 56 Fe) radiation stopped in a thick aluminum shield was measured at different angles with a GSI neutron ball, the standard TLD (thermoluminescent dosimeters)-based neutron dosimeter for area monitoring at the GSI facility. In order to measure reliably at large angles, a modified version of the GSI ball, including a set of three more sensitive TLD600H/700H cards, instead of one standard TLD600/700 card was used. The modified GSI ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…First experiments with 1 GeV/u 56 Fe ions on a thick aluminum target have been carried out in Cave A at GSI Helmholtzzentrum für Schwerionenforschung in Darmstadt, Germany, in the framework of the IBER program funded by ESA. The results obtained with the TLDbased detector systems are already published [13,15] and the measurement data from the other methods are currently being analyzed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First experiments with 1 GeV/u 56 Fe ions on a thick aluminum target have been carried out in Cave A at GSI Helmholtzzentrum für Schwerionenforschung in Darmstadt, Germany, in the framework of the IBER program funded by ESA. The results obtained with the TLDbased detector systems are already published [13,15] and the measurement data from the other methods are currently being analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…This passive dosimeter, equipped with Harshaw TLD cards (one TLD-600H and one 700H pair), has a neutron response function close to fluence-to-ambient-dose conversion coefficients and, therefore, provides read-out values close to the ambient dose equivalent H* (10). First results for 1 GeV/u 56 Fe ions on a thick aluminum target have been published [13] and the dosimeter H*(10) readings were comparable with the predictions by the Monte Carlo code FLUKA.…”
Section: Tld-based Neutron Ambient Dosimeters and Bonner Spectrometermentioning
confidence: 99%
“…In addition to secondary neutrons, secondary protons are also of particular interest since they can interact with the metal shells of modified Bonner Spheres producing additional neutrons by nuclear spallation. The latter can thermalize and reach the CTNS creating parasitic counts [9,27] and consequently they must be subtracted to avoid overestimations. Simulations showed that secondary protons induced by the primary beam of protons and 4 He particles can be neglected since they contribute to the modified spheres responses at 0.24% and 1% for the 0 • measurement position, respectively, while for the 90 • position both contribute less than 0.01%.…”
Section: Simulated Neutron Fieldmentioning
confidence: 99%
“…However, studies of the secondary radiation fields performed with stochastic and deterministic transport codes are mainly based on physical models and not on empirical data given by differential cross sections [8]. In recent years, many studies of secondary neutrons produced by the interaction of high-energy ions with space-relevant materials are being conducted to fill this data gap [9][10][11]. This scarcity of experimental data is mainly due to the low number of facilities capable of accelerating ions to energies relevant for the study of GCR effects.…”
mentioning
confidence: 99%
“…Despite the inherent challenges associated with handling and stability, hydrogen is regarded as the most efficacious element in terms of shielding effectiveness per unit mass density [6,13]. Aluminum (Al) Polyethylene (PE), Kevlar, Nextel, Nomex, Lucite have demonstrated shielding capabilities in accelerator beam experiments [7,[14][15][16][17][18][19][20][21][22][23][24][25]. Studies have been conducted on the International Space Station (ISS) to investigate the reduction of dose by employing water blocks, polyethylene (PE) blocks, and packages made from water soaked sanitary towels [26][27][28].…”
Section: Introductionmentioning
confidence: 99%